Opportunities to grab for Malaysian women entrepreneurships - Mohamed Isa, Zuraidah; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2009)
There are growing women entrepreneurs in Malaysia. These women entrepreneurs play major roles in promoting the development of Malaysia economic. And these women entrepreneurs help providing job opportunities to Malaysian. Knowing their importance in economics of Malaysia, Government of Malaysia has arranged numbers of programs and incentive to promote the development of these women entrepreneurs. As a result there emerged numbers of associations who are willing to help and give support to these women entrepreneurs. This paper intends to discuss the scenario of today’s women entrepreneurs and associations which support the development of these women entrepreneurs and opportunities to grab off these women entrepreneurs.